Clopidogrel plus aspirin versus aspirin alone for reducing embolisation in patients with acute symptomatic cerebral or carotid artery stenosis (CLAIR study): A randomised, open-label, blinded-endpoint trial - Wong, K.S.L.; Chen, C.; Fu, J.; Chang, H.M.; Suwanwela, N.C.; Huang, Y.N.; Han, Z.; Tan, K.S.; Ratanakorn, D.; Chollate, P.; Zhao, Y.; Koh, A.; et al. (Elsevier, 2010)
Background Few randomised clinical trials have investigated the use of antithrombotic drugs for early secondary prevention of stroke or transient ischaemic attack in patients with intracranial atherosclerotic stenosis. Microembolic signals, detected by transcranial doppler, are a surrogate marker of future stroke risk and have been used to show treatment efficacy in patients with extracranial carotid stenosis. We aimed to investigate whether treatment with clopidogrel plus aspirin reduced the number of microembolic signals detected with transcranial doppler ultrasound compared with aspirin alone in patients with recent stroke. Methods The clopidogrel plus aspirin for infarction reduction in acute stroke or transient ischaemic attack patients with large artery stenosis and microembolic signals (CLAIR) trial was a randomised, open-label, blinded-endpoint trial. Between Oct 28,2003, and Nov 19,2008, patients with acute ischaemic stroke or transient ischaemic attack who had symptomatic large artery stenosis in the cerebral or carotid arteries and in whom microembolic signals were present on transcranial doppler were randomly assigned within 7 days of symptom onset to receive clopidogrel (300 mg for the first day, then 75 mg daily) plus aspirin (75-160 mg daily) or aspirin alone (75-160 mg daily) for 7 days. Patients were randomly assigned in blocks of four or six by use of a randomisation website. Monitoring of microembolic signals on transcranial doppler was done on days 2 and 7. The primary endpoint was the proportion of patients who had microembolic signals on day 2. Analysis was by modified intention to treat. All analyses were done by an investigator masked to both patient identity and the day the recording was taken. This trial is registered with the Centre for Clinical Trials, Chinese University of Hong Kong, number CUHK_CCT00164. Findings 100 patients were randomly assigned to clopidogrel plus aspirin (n=47) or aspirin monotherapy (n=53). 93 of 100 patients had symptomatic intracranial stenosis in either the intracranial internal carotid artery or the middle cerebral artery: 45 of 46 in the dual therapy group and 48 of 52 in the monotherapy group. At day 2,14 of 45 patients in the dual therapy group and 27 of 50 patients in the monotherapy group for whom data were available had at least one microembolic signal on transcranial doppler (relative risk reduction 42.4%, 95% CI 4.6-65.2; p=0.025). Adverse events were similar in the two groups. No patients had intracranial or severe systemic haemorrhage, but two patients in the dual therapy group had minor haemorrhages. Interpretation Combination therapy with clopidogrel and aspirin is more effective than aspirin alone in reducing microembolic signals in patients with predominantly intracranial symptomatic stenosis. Clinical trials are now warranted to investigate whether this combination treatment also results in a reduction in stroke incidence.